Das plantas aos ossos: a paleodieta através de isótopos estáveis de δ13C e δ15N e microvestígios arqueobotânicos para compreensão de grupos humanos pré-coloniais no Nordeste do Brasil - Carvalho, Luzia Maria de Sousa (2023)
This thesis aimed to recover and organize the data for the identification of the paleodiet from the pre-colonial population that inhabited the Northeast of Brazil. It aims to understand the biocultural practices around the management of vegetables, the agricultural practices, knowledge about the native plants and their purpose given, from medicinal to ritual purposes. In addition, the consumption of animal protein, and consequently a better understanding of the ways of life of these populations through food analysis. The research was carried out through analysis and recovery of microtraces of higher plants: starch grains, present and recovered in dental calculus samples. Stable isotope ratios of carbon (d13C) and nitrogen (d15N) were also identified in samples of human remains, such as bones and teeth, belonging to the burials of the Furna do Estrago Archaeological Site/PE, Barra Archeological Site/PB correlated with the Toca da Baixa dos Caboclos Archaeological Site/PI. Different aspects of resources available and plant management were observed on a time scale over thousands of years. The analysis of plant microtraces showed an intense and diversified use of plants for diverse purposes as feeding, pharmacologic, aromatic, and ritualistic. Among which it was possible to identify the families (Convolvulaceae, Anacardiaceae, Poaceae, Euphorbiaceae) and botanical species (Ipomoea batatas, Capsicum sp., Astronium fraxinifolium, Zea mays, Manihot esculenta), among others. Such data were compiled and confirmed by the methods of stable isotopes of carbon (d13C), identified through fragments of bones and teeth, which showed the ingestion of C3 plants, such as corn and other cultivated grasses, and C4 plants, such as cassava, jam and other tubers, and through nitrogen (d15N) the ingestion of animal protein of high trophic level in the food chain was identified. These data contributed to the understanding of domestic and funeral practices, corroborating the hypothesis of a sedentary lifestyle on the part of these populations studied. In this way, leading for a better understanding about the lifestyle in which these populations lived and the means of subsistence common among different groups that inhabited the northeastern sertão in past times. Also acquiring data on the environmental context of flora in which they nhabited and their use of the plants, thus acquiring valuable information on the study of paleodiet of these populations associated with ways of life in the context of sedentary occupations, plant domestication and dietary patterns in a regional contex.